A Method for Determination of Metals in Hybrid Metal Oxide/Metal-Carbon Nanotubes Catalysts - Joanna Bok-Badura; Agata Jakóbik-Kolon; Agata Łamacz; Krzysztof Karoń (Journal of Chemistry)
Carbon nanotubes (CNTs), due to their special structure and unique properties, are still one of the most interesting materials for scientists. Recently, carbon nanotubes were proposed as a new type of carbon support for catalysts. Fe, Pt, Ni, Co, and other metals anchored to CNTs are used in various reactions. Due to the fact that production processes are usually unpredictable and the total amount of metal/metal oxide deposited on the CNTs may only be estimated, the methods for examining the chemical composition are necessary. In this study, fast and simple inductively coupled plasma atomic emission spectrometry (ICP-AES) with slurry nebulization was proposed for metal content determination in hybrid CeZrO2/CNT, Ni-CeZrO2/CNT, and Ni/CNT materials. Slurries were prepared by 30 min ultrasonication of appropriate amount of investigated material in 1% Triton X-100 solution. Optimal range of slurry concentration and optimal RF plasma power were established (40–400 mg L−1, 1.2 kW, resp.). Obtained results proved that this method may be applied for determination of Ce, Zr, and Ni in hybrid CNT-based materials.